Formula and manufacturing method of motor soft magnetic material for new energy automobile

The soft magnetic materials for motors for new energy vehicles prepared through specific formulas and process steps have solved the problems of poor thermal insulation, high coercivity, low magnetic permeability and insufficient wear resistance of existing materials, and achieved excellent thermal insulation performance, low coercivity, high magnetic permeability and good lubricating effect, ensuring the quality of the finished product.

CN119650234APending Publication Date: 2025-03-18DONGGUAN ANSTEED ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839672.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing soft magnetic materials for motors for new energy vehicles have poor thermal insulation, poor coerciveness and magnetic permeability, easy to stick when demolding, insufficient wear resistance, and affect the quality of the finished product.

Method used

It is prepared by annealing, crushing, screening, mixing, pressing, heat treatment and spraying, and other processes such as annealing, crushing, screening, mixing, pressing, heat treatment and spraying.

Benefits of technology

It significantly improves the thermal insulation performance of the material, reduces coercivity, improves magnetic permeability, enhances lubricating effect, avoids adhesion, improves the wear resistance of the material, and ensures the quality of the finished product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a motor soft magnetic material for a new energy automobile. The material is prepared from the following components in parts by weight: 6.1 to 9.8 weight percent of silicon, 5.1 to 5.9 weight percent of aluminum, 4.3 to 4.7 weight percent of cobalt, 65 to 81.4 weight percent of iron, 4 to 30 weight percent of reinforced fiber, 4 to 30 weight percent of friction performance regulator, 4 to 7 weight percent of modified stearic acid release agent and 2 to 5 weight percent of nano high-temperature-resistant coating. According to the invention, the motor soft magnetic material is coated with the nano high-temperature-resistant coating, so that relatively strong chemical bonds and lattice distortion can be formed in the material, heat conduction is blocked, heat radiation can be absorbed, and the material has relatively low heat conductivity, so that the heat insulation performance is excellent. Meanwhile, the crystallization volume fraction is increased through the technological method, the shape of a hysteresis loop of the material is changed, the coercive force in the material is greatly reduced, the magnetic conductivity is improved, the wear resistance of the motor soft magnetic material is improved, and the quality of a finished product is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soft magnetic materials, and in particular to a formula of soft magnetic material for motors of new energy vehicles and a method for manufacturing the same. Background Art

[0002] With the popularity of new energy vehicles, soft magnetic materials for motors used in new energy vehicles have received extensive attention. Composite soft magnetic materials refer to a type of soft magnetic material in which magnetic powders are independent of each other and connected by insulating layer materials. The outstanding advantages of this composite soft magnetic material are low iron loss and three-dimensional isotropic properties under AC magnetic field. Therefore, many components that are difficult to achieve with conventional soft magnetic materials can be prepared, and have been applied in the fields of switch reluctance, resonant inductance, anti-lock brake sensor, electromagnetic drive device, brushless DC motor, rotating machinery, low-frequency filter, etc. The preparation process of composite soft magnetic materials is usually to coat the surface of metal or alloy magnetic powder with inorganic and organic electrical insulation layers, or to form composite soft magnetic powders by composite method of magnetic powder matrix-high resistivity continuous fiber, and then to prepare dense block soft magnetic materials by powder metallurgy compaction process. However, the existing soft magnetic composite materials have poor thermal insulation, and the coercive force and magnetic permeability of the materials still cannot achieve good performance. Adhesion is easy to occur during demolding, the material has poor wear resistance, and the quality of the finished product cannot be effectively guaranteed. Summary of the invention

[0003] The purpose of the present invention is to provide a method to solve the problems raised in the above background technology.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a soft magnetic material for motors of new energy vehicles, the material formula consisting of the following components in parts by weight: 6.1-9.8wt% silicon, 5.1-5.9wt% aluminum, 4.3-4.7wt% cobalt, 65-81.4wt% iron, 4-30wt% reinforcing fiber, 4-30wt% friction performance regulator, 4-7wt% modified stearic acid release agent, and 2-5wt% nano high temperature resistant coating.

[0005] Preferably, the reinforcing fiber is one or any combination of glass fiber, sepiolite fiber, needle-shaped wollastonite, fibrous brucite, aluminum silicate fiber, and rock wool.

[0006] Preferably, the friction performance regulator is one or any combination of feldspar, barite, wollastonite, fluorite, cryolite, iron oxide, chromite powder, aluminum oxide, zircon, quartzite, corundum, vermiculite, zeolite, limestone, kaolin, diatomaceous earth, and dolomite.

[0007] Preferably, the modified stearic acid-based release agent is one or more of modified zinc stearate, modified aluminum stearate, modified magnesium stearate, modified calcium stearate or modified lithium stearate.

[0008] Preferably, the preparation method of the modified stearic acid release agent is as follows: S1: weigh 8-14g of aluminum hydroxide, add 100-186mL of water to prepare a slurry with a mass fraction of 4-7%; S2: add 130-160g of magnesium stearate to the slurry, heat and stir; S3: after constant temperature reaction for 3-5h, filter and wash, and dry at 90-110°C to obtain modified magnesium stearate; in S2, the heating rate is 5-8°C / min, the initial temperature is 20-22°C, the maximum temperature is 100-110°C, and the stirring speed is 30-60r / min.

[0009] Preferably, the raw materials of the nano high temperature resistant coating include, by weight: 80 to 100 parts of nano rare earth powder, 8 to 16 parts of hyperbranched polyamide, 0.5 to 5 parts of hydrophilic nano silica, 10 to 30 parts of flame retardant, 30 to 50 parts of resin, 0.5 to 3 parts of organic bentonite, 1 to 5 parts of wetting dispersant, 2 to 8 parts of acetone, and 1 to 6 parts of sodium dodecyl sulfate.

[0010] Preferably, the nano rare earth powder is prepared by mixing nano lanthanum hexaboride powder, nano gadolinium oxide powder, nano lanthanum oxide powder and nano dysprosium oxide powder.

[0011] A method for manufacturing a soft magnetic material for a motor of a new energy vehicle comprises the following preparation steps:

[0012] Step S1, raw material preparation: mixing according to the required ingredients, the raw materials include: silicon 9.1-9.8wt%, aluminum 5.1-5.9wt%, cobalt 4.3-4.7wt%, iron 50-81.4wt%;

[0013] Step S2, primary annealing: annealing various soft magnetic materials respectively, and feeding the materials into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of Ar+CO to make the gas constant pressure in the vacuum annealing furnace 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 25℃ / min~40℃ / min, so that the material quickly cools to room temperature;

[0014] Step S3, secondary annealing: take out the blank after annealing in step S2, and then send it into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to -0.1Mpa; then introduce a mixed gas of CO2+H2 to make the gas pressure constant at 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; lower the temperature of the temperature controller, introduce compressed cold air to quickly cool down, the cooling rate is 25°C / min~40°C / min, so that the material quickly drops to a certain temperature, keep the temperature, turn off the heating device, and introduce compressed cold air to quickly cool down, the cooling rate is 25°C / min~40°C / min, so that the material quickly drops to room temperature;

[0015] Step S4, mixing: crush the block material after annealing in step S3 into fine powder by a crusher, screen the soft magnetic materials respectively, add 4-30wt% of reinforcing fiber, 4-30wt% of friction performance regulator, and 4-7wt% of modified stearic acid release agent to the mixture, and put the materials into a mixer for high-speed mixing for 15-30min;

[0016] Step S5, pressing: placing the mixture obtained in step S4 into a mold, and then pressing and molding at a temperature of 20° C. to 90° C. and a mechanical pressure of 400 MPa to 2500 MPa to obtain a blank of the composite soft magnetic material;

[0017] Step S6, heat treatment: performing a protective atmosphere heat treatment or a vacuum heat treatment on the composite soft magnetic material blank obtained in step S5, so as to obtain a composite soft magnetic material;

[0018] Step S7, spraying: spraying the material obtained after the heat treatment in step S6 with nano high temperature resistant coating.

[0019] Preferably, the protective atmosphere heat treatment described in step S6 is specifically performed as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed in a nitrogen, argon or hydrogen atmosphere, and then the temperature is increased to 200°C to 900°C at a heating rate of 8°C / min to 12°C / min, and the blank of the composite soft magnetic material obtained in step S5 is heat treated for 10min to 300min under the protection of nitrogen, argon or hydrogen and at a temperature of 200°C to 900°C, and then the temperature is reduced to room temperature at a cooling rate of 8°C / min to 12°C / min, so as to obtain a composite soft magnetic material;

[0020] Preferably, the vacuum heat treatment described in step S6 is specifically performed as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed under vacuum conditions, and then the temperature is increased to 200°C to 900°C at a heating rate of 8°C / min to 12°C / min, and the blank of the composite soft magnetic material obtained in step S5 is heat treated for 10min to 300min under the conditions of a vacuum degree of -0.1Mpa and a temperature of 200°C to 900°C, and then the temperature is reduced to room temperature at a cooling rate of 8°C / min to 12°C / min to obtain a composite soft magnetic material.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: by coating the motor soft magnetic material with nano-high temperature resistant coating, the present invention can form strong chemical bonds and lattice distortion in the material, thereby blocking heat conduction, and can absorb heat radiation, with low thermal conductivity, and thus excellent thermal insulation performance. At the same time, the present invention increases the crystallization volume fraction and changes the shape of the material hysteresis loop through a process method, greatly reducing the coercive force in the material, improving the magnetic permeability, and also improving the lubrication effect, facilitating demoulding, avoiding the phenomenon of bonding, so that the non-stickiness is improved, and the wear resistance of the motor soft magnetic material is improved, and the quality of the finished product is guaranteed. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] The invention provides a soft magnetic material for a motor of a new energy vehicle. The material formula consists of the following components in parts by weight: 6.1wt% of silicon, 5.1wt% of aluminum, 4.3wt% of cobalt, 68.5wt% of iron, 5wt% of glass fiber, 5wt% of feldspar, 4wt% of modified magnesium stearate, and 2t% of nano-high temperature resistant coating.

[0025] The preparation method of modified magnesium stearate is as follows: S1: weigh 8g of aluminum hydroxide and add 100mL of water to prepare a slurry with a mass fraction of 4%; S2: add 130g of magnesium stearate to the slurry, heat and stir;

[0026] S3: After constant temperature reaction for 3 hours, filter and wash, and dry at 90°C to obtain modified magnesium stearate; in S2, the heating rate is 5°C / min, the initial temperature is 20°C, the maximum temperature is 100°C, and the stirring speed is 30r / min.

[0027] The raw materials of the nano high-temperature resistant coating include, by weight: 80 parts of nano rare earth powder, 8 parts of hyperbranched polyamide, 0.5 parts of hydrophilic nano silica, 10 parts of flame retardant, 30 parts of water-based polyurethane resin, 0.5 parts of organic bentonite, 1 part of calcium carbonate, 2 parts of acetone, and 1 part of sodium dodecyl sulfate.

[0028] The flame retardant is prepared by mixing zinc borate, antimony trioxide, magnesium hydroxide and aluminum hydroxide, and the ratio of zinc borate, antimony trioxide, magnesium hydroxide and aluminum hydroxide is 1:1:1:1.

[0029] The nano rare earth powder is prepared by mixing nano lanthanum hexaboride powder, nano gadolinium oxide powder, nano lanthanum oxide powder and nano dysprosium oxide powder in a ratio of 1:1:1:1.

[0030] A method for manufacturing a soft magnetic material for a motor of a new energy vehicle comprises the following preparation steps:

[0031] Step S1, raw material preparation: prepare the ingredients according to the required ingredients;

[0032] Step S2, primary annealing: annealing various soft magnetic materials respectively, and feeding the materials into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of Ar+CO to make the gas constant pressure in the vacuum annealing furnace 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 25°C / min, so that the material quickly drops to room temperature;

[0033] Step S3, secondary annealing: take out the blank after annealing in step S2, and then send it into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to -0.1Mpa; then introduce a mixed gas of CO2+H2 to make the gas pressure constant at 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; lower the temperature of the temperature controller, introduce compressed cold air to quickly cool down, the cooling rate is 25°C / min, so that the material quickly drops to a certain temperature, keep the temperature, turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 25°C / min, so that the material quickly drops to room temperature;

[0034] Step S4, mixing: crush the block material after annealing in step S3 into fine powder by a crusher, screen the soft magnetic materials respectively, add 5wt% of glass fiber, 5wt% of feldspar, and 4wt% of modified magnesium stearate to the mixture, and put the materials into a mixer for high-speed mixing for 15 minutes;

[0035] Step S5, pressing: putting the mixture obtained in step S4 into a mold, and then pressing and molding at a temperature of 20° C. and a mechanical pressure of 400 MPa to obtain a blank of the composite soft magnetic material;

[0036] Step S6, heat treatment: performing a protective atmosphere heat treatment or a vacuum heat treatment on the composite soft magnetic material blank obtained in step S5, so as to obtain a composite soft magnetic material;

[0037] Step S7, spraying: spraying the material obtained after the heat treatment in step S6 with nano high temperature resistant coating.

[0038] The specific operation of the protective atmosphere heat treatment described in step S6 is as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed in a nitrogen, argon or hydrogen atmosphere, and then the temperature is increased to 500°C at a heating rate of 8°C / min, and the blank of the composite soft magnetic material obtained in step S5 is heat treated for 10 minutes under the protection of nitrogen, argon or hydrogen and at a temperature of 500°C, and then the temperature is cooled to room temperature at a cooling rate of 8°C / min to obtain the composite soft magnetic material.

[0039] The specific operation of the vacuum heat treatment described in step S6 is as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed under vacuum conditions, and then the temperature is increased to 200°C at a heating rate of 8°C / min. The blank of the composite soft magnetic material obtained in step S5 is heat treated for 10 minutes under vacuum conditions of -0.1Mpa and temperature of 200°C, and then the temperature is cooled to room temperature at a cooling rate of 8°C / min to obtain the composite soft magnetic material.

[0040] Example 2

[0041] The difference from Example 1 is that: the present invention provides a technical solution, and the material formula consists of the following components in weight parts: 6.1wt% silicon, 5.1wt% aluminum, 4.3wt% cobalt, 65.5wt% iron, 6wt% sepiolite fiber, 5wt% barite, 5wt% modified aluminum stearate, and 3t% nano high temperature resistant coating.

[0042] The preparation method of modified aluminum stearate is as follows: S1: weigh 14g aluminum hydroxide, add 186mL water to prepare a slurry with a mass fraction of 7%; S2: add 160g aluminum stearate to the slurry, heat and stir;

[0043] S3: After isothermal reaction for 5 hours, filter and wash, and dry at 110°C to obtain modified aluminum stearate; in S2, the heating rate is 8°C / min, the initial temperature is 22°C, the maximum temperature is 110°C, and the stirring speed is 60r / min.

[0044] The raw materials of the nano high-temperature resistant coating include, by weight: 85 parts of nano rare earth powder, 12 parts of hyperbranched polyamide, 3 parts of hydrophilic nano silica, 20 parts of flame retardant, 40 parts of water-based polyurethane resin, 2 parts of organic bentonite, 3 parts of calcium carbonate, 4 parts of acetone, and 3 parts of sodium dodecyl sulfate.

[0045] The flame retardant is prepared by mixing zinc borate, antimony trioxide, magnesium hydroxide and aluminum hydroxide, and the ratio of zinc borate, antimony trioxide, magnesium hydroxide and aluminum hydroxide is 1:1:1:1.

[0046] The nano rare earth powder is prepared by mixing nano lanthanum hexaboride powder, nano gadolinium oxide powder, nano lanthanum oxide powder and nano dysprosium oxide powder in a ratio of 1:1:1:1.

[0047] A method for manufacturing a soft magnetic material for a motor of a new energy vehicle comprises the following steps:

[0048] Step S1, raw material preparation: prepare the ingredients according to the required ingredients;

[0049] Step S2, primary annealing: annealing various soft magnetic materials respectively, and feeding the materials into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of Ar+CO to make the gas constant pressure in the vacuum annealing furnace 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; turn off the heating device, introduce compressed cold air to quickly cool down, and the cooling rate is 40°C / min, so that the material quickly drops to room temperature;

[0050] Step S3, secondary annealing: take out the blank after annealing in step S2, and then send it into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of CO2+H2 to make the gas pressure constant at 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; lower the temperature of the temperature controller, introduce compressed cold air to quickly cool down, the cooling rate is 40°C / min, so that the material quickly drops to a certain temperature, keep the temperature, turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 40°C / min, so that the material quickly drops to room temperature;

[0051] Step S4, mixing: crush the block material after annealing in step S3 into fine powder by a crusher, screen the soft magnetic materials respectively, add 6wt% of sepiolite fiber, 5wt% of barite, and 5wt% of modified aluminum stearate to the mixture, and put the materials into a mixer for high-speed mixing for 30 minutes;

[0052] Step S5, pressing: putting the mixture obtained in step S4 into a mold, and then pressing and molding at a temperature of 90° C. and a mechanical pressure of 2500 MPa to obtain a blank of the composite soft magnetic material;

[0053] Step S6, heat treatment: performing a protective atmosphere heat treatment or a vacuum heat treatment on the composite soft magnetic material blank obtained in step S5, so as to obtain a composite soft magnetic material;

[0054] Step S7, spraying: spraying the material obtained after the heat treatment in step S6 with nano high temperature resistant coating.

[0055] The specific operation of the protective atmosphere heat treatment described in step S6 is as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed in a nitrogen, argon or hydrogen atmosphere, and then the temperature is increased to 900°C at a heating rate of 12°C / min, and the blank of the composite soft magnetic material obtained in step S5 is heat treated for 300 minutes under the protection of nitrogen, argon or hydrogen and at a temperature of 900°C, and then the temperature is cooled to room temperature at a cooling rate of 12°C / min to obtain the composite soft magnetic material.

[0056] Specifically, the vacuum heat treatment described in step S6 is specifically operated as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed under vacuum conditions, and then the temperature is increased to 900°C at a heating rate of 12°C / min, and the blank of the composite soft magnetic material obtained in step S5 is heat treated for 300 minutes under vacuum conditions of -0.1Mpa and a temperature of 900°C, and then the temperature is cooled to room temperature at a cooling rate of 12°C / min to obtain the composite soft magnetic material.

[0057] Example 3

[0058] The difference from the above embodiment is that: the present invention provides a soft magnetic material for motors for new energy vehicles, and the material formula is composed of the following components in weight: 6.1wt% silicon, 5.1wt% aluminum, 4.3wt% cobalt, 65.5wt% iron, 4wt% needle-shaped wollastonite, 6wt% wollastonite, 5wt% modified zinc stearate, and 4wt% nano high-temperature resistant coating.

[0059] The preparation method of modified zinc stearate is as follows: S1: weigh 10g of aluminum hydroxide and add 140mL of water to prepare a slurry with a mass fraction of 5%; S2: add 150g of zinc stearate to the slurry, heat and stir;

[0060] S3: After constant temperature reaction for 4 hours, filter and wash, and dry at 100°C to obtain modified zinc stearate; in S2, the heating rate is 6°C / min, the initial temperature is 21°C, the maximum temperature is 105°C, and the stirring speed is 45r / min.

[0061] The raw materials of the nano high-temperature resistant coating include, by weight: 90 parts of nano rare earth powder, 16 parts of hyperbranched polyamide, 4 parts of hydrophilic nano silica, 30 parts of flame retardant, 50 parts of water-based polyurethane resin, 3 parts of organic bentonite, 4 parts of calcium carbonate, 7 parts of acetone, and 5 parts of sodium dodecyl sulfate.

[0062] The flame retardant is prepared by mixing zinc borate, antimony trioxide, magnesium hydroxide and aluminum hydroxide, and the ratio of zinc borate, antimony trioxide, magnesium hydroxide and aluminum hydroxide is 1:1:1:1.

[0063] The nano rare earth powder is prepared by mixing nano lanthanum hexaboride powder, nano gadolinium oxide powder, nano lanthanum oxide powder and nano dysprosium oxide powder in a ratio of 1:1:1:1.

[0064] A method for manufacturing a soft magnetic material for a motor of a new energy vehicle comprises the following steps:

[0065] Step S1, raw material preparation: prepare the ingredients according to the required ingredients;

[0066] Step S2, primary annealing: annealing various soft magnetic materials respectively, and feeding the materials into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of Ar+CO to make the gas constant pressure in the vacuum annealing furnace 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 390℃ / min, so that the material quickly drops to room temperature;

[0067] Step S3, secondary annealing: take out the blank after annealing in step S2, and then send it into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to -0.1Mpa; then introduce a mixed gas of CO2+H2 to make the gas pressure constant at 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; lower the temperature of the temperature controller, introduce compressed cold air to quickly cool down, the cooling rate is 30°C / min, so that the material quickly drops to a certain temperature, keep the temperature, turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 30°C / min, so that the material quickly drops to room temperature;

[0068] Step S4, mixing: crush the block material after annealing in step S3 into fine powder by a crusher, screen the soft magnetic materials respectively, add 4wt% of needle-shaped wollastonite, 6wt% of wollastonite, and 5wt% of modified zinc stearate to the mixture, and put the materials into a mixer for high-speed mixing for 20 minutes;

[0069] Step S5, pressing: putting the mixture obtained in step S4 into a mold, and then pressing and molding it at a temperature of 50° C. and a mechanical pressure of 1500 MPa to obtain a blank of the composite soft magnetic material;

[0070] Step S6, heat treatment: performing a protective atmosphere heat treatment or a vacuum heat treatment on the composite soft magnetic material blank obtained in step S5, so as to obtain a composite soft magnetic material;

[0071] Step S7, spraying: spraying the material obtained after the heat treatment in step S6 with nano high temperature resistant coating.

[0072] Specifically, the protective atmosphere heat treatment described in step S6 is specifically performed as follows: first, the composite soft magnetic material blank obtained in step S5 is placed in a nitrogen, argon or hydrogen atmosphere, and then the temperature is increased to 500°C at a heating rate of 12°C / min, and the composite soft magnetic material blank obtained in step S5 is heat treated for 100 minutes under the protection of nitrogen, argon or hydrogen and at a temperature of 500°C, and then the temperature is cooled to room temperature at a cooling rate of 12°C / min to obtain the composite soft magnetic material.

[0073] The specific operation of the vacuum heat treatment described in step S6 is as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed under vacuum conditions, and then the temperature is increased to 500°C at a heating rate of 12°C / min. The blank of the composite soft magnetic material obtained in step S5 is heat treated for 100 minutes under the conditions of a vacuum degree of -0.1Mpa and a temperature of 500°C, and then the temperature is cooled to room temperature at a cooling rate of 12°C / min to obtain a composite soft magnetic material.

[0074] The control group uses 9.8% silicon, 5.9% aluminum, 4.7% cobalt, and 79.6% iron; each of the soft magnetic materials is annealed once, the annealed soft magnetic materials are sieved, the sieved soft magnetic materials are evenly mixed, and pressed into motor soft magnetic materials.

[0075] The material performance parameters prepared in the above implementation cases were tested for thermal insulation performance using a TPP thermal protection performance tester, and the LE coercive force tester was used to magnetize the sample through a solenoid magnetizing coil. At the same time, a Gaussmeter transverse probe close to the sample detected the stray magnetic field emitted by the magnetized sample, and then the sample was demagnetized using a demagnetization coil until the Gaussmeter reading was zero. Under this condition, the demagnetization magnetic field is equal to the coercive force. CR / 01 is an automated measurement using easy-to-operate software, and this measurement meets the IEC60404-7 international standard. Observe whether the surface of the blank of the composite soft magnetic material obtained when the mixture is demolded in step S5 is adhered. The test results are as follows:

[0076]

[0077] From the data, it can be seen that the coated motor soft magnetic material can meet the thermal insulation requirements, and the coercive force is <3.0×10 5 A / m, maximum magnetic permeability μ i All are greater than 30000. Therefore, the motor soft magnetic material coated with the thermal insulation nano coating has excellent thermal insulation performance, reduces the coercive force in the material, increases the magnetic permeability, and can also enhance the lubrication effect.

[0078] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A soft magnetic material for motors used in new energy vehicles, characterized in that: The material formula consists of the following components in parts by weight: 6.1-9.8wt% silicon, 5.1-5.9wt% aluminum, 4.3-4.7wt% cobalt, 65-81.4wt% iron, 4-30wt% reinforcing fiber, 4-30wt% friction performance regulator, 4-7wt% modified stearic acid release agent, and 2-5wt% nano high temperature resistant coating.

2. The soft magnetic material for motors for new energy vehicles according to claim 1, characterized in that: The reinforcing fiber is one or any combination of glass fiber, sepiolite fiber, needle-shaped wollastonite, fibrous brucite, aluminum silicate fiber and rock wool.

3. The soft magnetic material for motors for new energy vehicles according to claim 1, characterized in that: The friction performance regulator is one or any combination of feldspar, barite, wollastonite, fluorite, cryolite, iron oxide, chromite powder, aluminum oxide, zircon, quartzite, corundum, vermiculite, zeolite, limestone, kaolin, diatomaceous earth and dolomite.

4. The soft magnetic material for motors for new energy vehicles according to claim 1, characterized in that: The modified stearic acid-based release agent is one or more of modified zinc stearate, modified aluminum stearate, modified magnesium stearate, modified calcium stearate or modified lithium stearate.

5. The soft magnetic material for motors for new energy vehicles according to claim 4, characterized in that: The preparation method of the modified stearic acid release agent is as follows: S1: weigh 8-14g of aluminum hydroxide, add 100-186mL of water to prepare a slurry with a mass fraction of 4-7%; S2: add 130-160g of magnesium stearate to the slurry, heat and stir; S3: after constant temperature reaction for 3-5h, filter and wash, and dry at 90-110°C to obtain modified magnesium stearate; in S2, the heating rate is 5-8°C / min, the initial temperature is 20-22°C, the maximum temperature is 100-110°C, and the stirring speed is 30-60r / min.

6. The soft magnetic material for motors for new energy vehicles according to claim 1, characterized in that: The raw materials of the nano high-temperature resistant coating include, by weight: 80-100 parts of nano rare earth powder, 8-16 parts of hyperbranched polyamide, 0.5-5 parts of hydrophilic nano silica, 10-30 parts of flame retardant, 30-50 parts of resin, 0.5-3 parts of organic bentonite, 1-5 parts of wetting dispersant, 2-8 parts of acetone, and 1-6 parts of sodium dodecyl sulfate.

7. The soft magnetic material for motors for new energy vehicles according to claim 6, characterized in that: The nano rare earth powder is prepared by mixing nano lanthanum hexaboride powder, nano gadolinium oxide powder, nano lanthanum oxide powder and nano dysprosium oxide powder.

8. The method for manufacturing the soft magnetic material for motors of new energy vehicles according to any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: Step S1, raw material preparation: mixing the ingredients according to the required components, the raw materials include: 6.1-9.8wt% silicon, 5.1-5.9wt% aluminum, 4.3-4.7wt% cobalt, and 65-81.4wt% iron; Step S2, primary annealing: annealing various soft magnetic materials respectively, and feeding the materials into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of Ar+CO to make the gas constant pressure in the vacuum annealing furnace 0.2Mpa; start the heating device, increase the temperature, and keep the temperature constant; turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 25℃ / min~40℃ / min, so that the material quickly cools to room temperature; Step S3, secondary annealing: take out the blank after annealing in step S2, and then send it into a vacuum annealing furnace to form a closed cavity in the entire vacuum annealing furnace, evacuate the vacuum to a vacuum degree of -0.1Mpa; then introduce a mixed gas of CO2+H2, control the gas flow rate to 200mL / min, and make the gas pressure constant at 0.2Mpa; start the heating device, heat up, and keep the temperature constant; lower the temperature of the temperature controller, introduce compressed cold air to quickly cool down, the cooling rate is 25℃ / min~40℃ / min, so that the material quickly drops to a certain temperature, keep the temperature, turn off the heating device, introduce compressed cold air to quickly cool down, the cooling rate is 25℃ / min~40℃ / min, so that the material quickly drops to room temperature; Step S4, mixing: crush the block material after annealing in step S3 into fine powder by a crusher, screen the soft magnetic materials respectively, add 4-30wt% of reinforcing fiber, 4-30wt% of friction performance regulator, and 4-7wt% of modified stearic acid release agent to the mixture, and put the materials into a mixer for high-speed mixing for 15-30min; Step S5, pressing: placing the mixture obtained in step S4 into a mold, and then pressing and molding at a temperature of 20° C. to 90° C. and a mechanical pressure of 400 MPa to 2500 MPa to obtain a blank of the composite soft magnetic material; Step S6, heat treatment: performing a protective atmosphere heat treatment or a vacuum heat treatment on the composite soft magnetic material blank obtained in step S5, so as to obtain a composite soft magnetic material; Step S7, spraying: spraying the material obtained after the heat treatment in step S6 with nano high temperature resistant coating.

9. The method for manufacturing the soft magnetic material for motors of new energy vehicles according to claim 8, characterized in that: The specific operation of the protective atmosphere heat treatment described in step S6 is as follows: first, the blank of the composite soft magnetic material obtained in step S5 is placed in a nitrogen, argon or hydrogen atmosphere, and then the temperature is increased to 200℃~900℃ at a heating rate of 8°C / min~12℃ / min, and the blank of the composite soft magnetic material obtained in step eight is heat treated for 10min~300min under the protection of nitrogen, argon or hydrogen and at a temperature of 200℃~900℃, and then the temperature is reduced to room temperature at a cooling rate of 8℃ / min~12℃ / min to obtain the composite soft magnetic material.

10. The method for manufacturing the soft magnetic material for motors of new energy vehicles according to claim 8, characterized in that: The specific operation of the vacuum heat treatment in step S6 is as follows: first, the composite soft magnetic material blank obtained in step S5 is placed under vacuum conditions, and then heated to 200°C to 900°C at a heating rate of 8°C / min to 12°C / min, and then heated to 100°C at a vacuum degree of 10°C. -1 Pa~10 - 3 The composite soft magnetic material blank obtained in step eight is heat treated for 10 min to 300 min at a temperature of 200°C to 900°C and then cooled to room temperature at a cooling rate of 8°C / min to 12°C / min to obtain the composite soft magnetic material.